2003
DOI: 10.1046/j.0268-9146.2003.01056.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a single nucleotide polymorphism map of porcine chromosome 2

Abstract: Single nucleotide polymorphism markers are developed on SSC2, predominantly on the p-arm. Several studies reported a quantitative trait loci (QTL) for backfat thickness in this region. Single nucleotide polymorphisms were identified by comparative re-sequencing of polymerase chain reaction (PCR) products from a panel of eight individuals. The panel consisted of five Large Whites (each from a different Dutch breeding company), a Meishan, a Pietrain and a Wild Boar. In total, 67 different PCR products were seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 31 publications
3
12
0
Order By: Relevance
“…Composition of the 39 new SNPs identified in this study was: 74% C/T or A/G, 21% A/T or G/C or A/C or G/T, and 5% others. This observation is comparable with previous studies [5,9].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Composition of the 39 new SNPs identified in this study was: 74% C/T or A/G, 21% A/T or G/C or A/C or G/T, and 5% others. This observation is comparable with previous studies [5,9].…”
Section: Discussionsupporting
confidence: 93%
“…This value is low compared with a similar study [9]. By directly sequencing PCR amplification products from genes on the porcine SNPs were already described in others porcine genes [1,7].…”
Section: Discussionmentioning
confidence: 65%
“…A forthcoming paper that focuses on millions of SNP in the chicken genome will be available soon in Nature. In the pig, a recently developed SNP map of chromosome 2 showed that the SNP density is much higher [18], which is in accordance with the present study.…”
Section: Discussionsupporting
confidence: 93%
“…In humans, several high resolution SNP maps have been created for several chromosomes or even the whole genome, providing useful resources for studies on haplotypes associated with human diseases [2,23,28]. Furthermore, an SNP map of porcine chromosome 2 has been reported [18], however such studies have not been performed in the chicken yet. Nevertheless the results of the Chicken Genome Project, which ended in February of 2004, (http://genome.wustl.edu/projects/chicken/) enable the utilization of the draft sequence to identify SNP.…”
Section: Introductionmentioning
confidence: 99%
“…PCR amplification and sequencing were performed essentially as described in Jungerius et al (2003) except that PCR reactions were done in 12 l and sequences were analysed on an ABI3730 automated sequencer.…”
Section: Bac Cloning and Sequencingmentioning
confidence: 99%